A “Window of Therapeutic Opportunity” for Anti-Cytokine Therapy in Patients With Coronavirus Disease 2019 - De Stefano, Ludovico; Bobbio-Pallavicini, Francesca; Manzo, Antonio; Montecucco, Carlomaurizio; Bugatti, Serena (Frontiers in Immunology, 2020)
The effects of cytokine inhibition in the different phases of the severe coronavirus disease 2019 (COVID-19) are currently at the center of intense debate, and preliminary results from observational studies and case reports offer conflicting results thus far. The identification of the correct timing of administration of anti-cytokine therapies and other immunosuppressants in COVID-19 should take into account the intricate relationship between the viral burden, the hyperactivation of the innate immune system and the adaptive immune dysfunction. The main challenge for effective administration of anti-cytokine therapy in COVID-19 will be therefore to better define a precise “window of therapeutic opportunity.” Only considering a more specific set of criteria able to integrate information on direct viral damage, the cytokine burden, and the patient’s immune vulnerability, it will be possible to decide, carefully balancing both benefits and risks, the appropriateness of using immunosuppressive drugs even in patients affected primarily by an infectious disease.